1999
DOI: 10.1136/gut.44.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adrenaline injection and bipolar electrocoagulation for the arrest of peptic ulcer bleeding

Abstract: Background-Peptic ulcers with active bleeding or a non-bleeding visible vessel require aggressive endoscopic treatment. Aims-To determine whether endoscopic adrenaline injection alone or contact probe therapy following injection is a suitable treatment for peptic ulcer bleeding. Methods-A total of 96 patients with active bleeding or non-bleeding visible vessels received adrenaline alone, bipolar electrocoagulation alone, or combined treatment (n=32 in each group). Results-Initial haemostasis was not achieved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 20 publications
(17 reference statements)
0
48
0
8
Order By: Relevance
“…Results of two small studies suggested benefi t of epinephrine plus bipolar electrocoagulation vs. bipolar electrocoagulation alone, but results with thermal monotherapy were poorer in these trials than most other studies ( 69,70 ). A larger high-quality study found that injection of thrombin plus heater probe was not better than heater probe alone ( 71 ).…”
Section: Epinephrine Therapy Should Not Be Used Alone If Used It Shmentioning
confidence: 99%
“…Results of two small studies suggested benefi t of epinephrine plus bipolar electrocoagulation vs. bipolar electrocoagulation alone, but results with thermal monotherapy were poorer in these trials than most other studies ( 69,70 ). A larger high-quality study found that injection of thrombin plus heater probe was not better than heater probe alone ( 71 ).…”
Section: Epinephrine Therapy Should Not Be Used Alone If Used It Shmentioning
confidence: 99%
“…Moreover, by inspecting the Forrest plots for rebleeding in the meta-analyses, it should be noted that only 5 of 22 studies registered significantly different results between the 2 endoscopic strategies. [18][19][20][21][22] This would indicate that there was significant heterogeneity among the studies concerning recurrent bleeding. Marmo et al [14] handled this heterogeneity by subgroup analysis and meta-regression, and found that the type of dual therapy applied and the post-hemostasis adjuvant therapy with PPIs could explain the heterogeneity.…”
Section: [13-15]mentioning
confidence: 99%
“…Marmo et al [14] handled this heterogeneity by subgroup analysis and meta-regression, and found that the type of dual therapy applied and the post-hemostasis adjuvant therapy with PPIs could explain the heterogeneity. The applicability of the meta-analysis by Calvet et al [13] could be limited by the fact that only a single study used omeprazole as adjuvant treatment, [20] presently considered as "modern" anti-secretory therapy. A much more valuable interpretation of their results would indicate that dual therapy was superior to epinephrine monotherapy when medical therapy other than PPIs was given.…”
Section: [13-15]mentioning
confidence: 99%
See 1 more Smart Citation
“…Novamente, o grupo em que houve a associação dos métodos apresentou uma menor taxa de ressangramento ( 6% versus 30% versus 35.5%). 19 Bianco et al em um ensaio randomizado (n = 114) demonstrou que a combinação de epinefrina e termocoagulação bipolar apresenta um melhor controle inicial do sangramento e do volume de transfusão, quando comparada à injeção isolada. 20 Bardou et al em 2003 afirmou a equivalência entre quaisquer métodos de termocoagulação, quando isolados.…”
Section: Termocoagulaçãounclassified